FRI0507 The relationship between 10-year cardiovascular risk scores and disease activity in patients with psoriatic arthritis. (15th June 2017) - Ikumi, N; Farkas, F; Szentpetery, A; Kirby, B; FitzGerald, O
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with an increased prevalence of cardiovascular (CV) disease 1 . This increase may in turn be due to a higher prevalence of traditional CV risk factors as well as to persistent inflammatory musculoskeletal and skin disease 2 . Disease activity in PsA may be assessed by the Composite Psoriatic Disease Activity Index (CPDAI) across 5 domains of involvement: peripheral joints, skin, entheses, dactylitis and spinal manifestations. Long-term CV risk is evaluated using several methods for general population. Objectives: (1) To describe CV risk factors and 10-year CV risk scores among patients with PsA; and (2) to correlate with baseline CPDAI in this longitudinal study Methods: PsA patients fulfilling the CASPAR criteria were enrolled consecutively from Rheumatology clinics. Fasting bloods were obtained for glucose, insulin, lipids. Patients underwent thorough physical examination, joint and skin assessments and completed questionnaires on health, depression/anxiety and quality of life. Four different CV risk scores were calculated: (1) Framingham Coronary risk score (FCS); (2) American College of Cardiology and American Heart Association (ACC/AHA) 10-year atherosclerotic cardiovascular disease (ASCVD) algorithm; (3) Systematic Coronary Risk Evaluation (SCORE) algorithm; and (4) QRISK2 (2016). CPDAI was calculated with CPDAI cutoff ≤4 representing low/minimal disease activity (LDA) or remission. CPDAI >4 represented active disease requiring treatment change. Results: 100 PsA patients were recruited with mean age 52.4 (±10.5) (male 55%). Mean disease duration for PsA was 17.9 (±10) years. 58 patients (age 52.4±9.6, male 60.3%) had CPDAI≤4 (LDA Gp) and 41 patients (age 52.4±11.9, male 48.8%) had CPDAI>4 (active Gp) at baseline. There were significantly more patients with BMI≥35 in active Gp, but mean BMI, waist/hip ratio, blood pressure, fasting glucose, insulin, lipids, and patients taking NSIADs, oral corticosteroid, Methotrexate and/or biologics treatment were otherwise similar compared to LDA Gp. Skin (Psoriasis Area Severity Index (PASI); Dermatology Life Assessment Questionnaire (DLQI)) assessments together with levels of inflammatory markers such as C-reactive protein (CRP) were also similar in both groups. More active Gp had enthesitis (58.5%) and acute dactylitis (14.6%) (P<0.01 and 0.02, respectively). The mean FCS, ASCVD, SCORE and QRISK2 were similar in both groups (8.5±7.1% vs. 6.2±6.9%, P=0.11; 8.9±8.5% vs. 7.8±7.9%, P=0.54; 2.2±2.6% vs. 2.0±2.7%, P=0.81; 11.2±9.2% vs. 11.3±11.%, P=0.97, LDA Gp and active Gp respectively). Interestingly, there were more smokers in LDA Gp (60.3% vs 39.0%; p=0.04) and this likely accounts for the higher number of LDA Gp patients with FCS>10%. Conclusions: We found similar prevalence of traditional CV risk factors and similar 10-year CV risk scores in PsA patients regardless of their CPDAI. Further correlation with measures of disease activity over time will be required. References: Ogdie A. ARD 2015. Eder L. ARD 2016. Disclosure of Interest: N. Ikumi: None declared, F. Farkas: None declared, A. Szentpetery: None declared, B. Kirby Grant/research support from: abbie, O. FitzGerald Grant/research support from: abbie, Pfizer, BMS, Consultant for: abbie, Pfizer, BMS, Celgene, Janssen, Novartis, UCB, Eli Lilly